Learning Model Using Audio Visual Media in High School Basketball Learning: Systematic Literature Review - Afaf Achmad Syahab; Ahmad Bahriyanto (Review of Education, Science, and Technology, 2025)
Learning basketball in high school requires an innovative approach so that students can understand the concepts of techniques, tactics, and rules of the game effectively. One of the approaches that is developing is the use of audio-visual media in the learning process of physical education. This study aims to systematically examine the audio-visual-based basketball learning model applied in high school through the Systematic Literature Review (SLR) method. The method used refers to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The article search process was carried out using the Publish or Perish application with the Google Scholar database in the range of 2020–2025. Of the 200 articles identified, only 6 met the inclusion criteria and were worth analysis. The results of the study show that the use of audio-visual media in basketball learning can improve understanding of basic techniques, learning motivation, student involvement, as well as psychomotor and cognitive learning outcomes. These findings confirm that the integration of audio-visual media is a relevant and effective learning strategy to improve the quality of basketball learning in high school.